2016
DOI: 10.1111/bjh.14160
|View full text |Cite
|
Sign up to set email alerts
|

Post‐thaw viability of cryopreserved peripheral blood stem cells (PBSC) does not guarantee functional activity: important implications for quality assurance of stem cell transplant programmes

Abstract: Standard quality assurance (QA) of cryopreserved peripheral blood stem cells (PBSC) uses post-thaw viable CD34(+) cell counts. In 2013, concerns arose at Great Ormond Street Hospital (GOSH) about 8 patients with delayed engraftment following myeloablative chemotherapy with cryopreserved cell rescue, despite adequate post-thaw viable cell counts in all cases. Root cause analysis was undertaken; investigations suggested the freeze process itself was a contributing factor to suboptimal engraftment. Experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…In 2016, Morgenstern et al [88] found several instances of patients with delayed engraftments despite sufficient post-thaw viability of CD34+ cells. Determining post-thaw functionality is thus an important step before moving into clinical trials.…”
Section: Preclinical Assays For Qualitymentioning
confidence: 99%
“…In 2016, Morgenstern et al [88] found several instances of patients with delayed engraftments despite sufficient post-thaw viability of CD34+ cells. Determining post-thaw functionality is thus an important step before moving into clinical trials.…”
Section: Preclinical Assays For Qualitymentioning
confidence: 99%
“…Both techniques should be considered complementary, and we don't know if the observed loss of CD34+ cells in some of our grafts would also have translated into a decreased stem cell potency, as it would be measured by functional assays . This problem has been addressed recently, following a detailed analysis of patients with delayed engraftment after ASCT …”
Section: Discussionmentioning
confidence: 99%
“…The latter effect could be due to the widespread supportive use of granulocyte colony‐stimulating factor (G‐CSF) after transplantation, facilitating ANC reconstitution, as well as to G‐CSF administration at time of apheresis, which “primes” CD34+ cells toward granulocyte differentiation . Although CD34+ cell counts are considered a reliable surrogate marker for engraftment, they do not provide any information on functional activity . Even though different studies have shown a good correlation of postthaw CD34+ counts and engraftment, assessment of CD34+ cell counts is exclusively performed before freezing in most centers.…”
mentioning
confidence: 99%
“…Post-thaw culture for 24 h was found to be effective in reparation of many of the cryo-induced abnormalities. A recent review of cryopreservation practices across UK centres applying slow cooling cryopreservation for peripheral blood stem cells identified differences in practices which were reported under the umbrella term 'cryopreservation' [63]. These combined studies highlight an important point for all cell therapy cryopreservation activities; this is that cryopreservation is not a simple 'standardised one option' process, the various protocol steps need to be well documented in standard operating procedures, and the equipment involved should be applied with care and monitored frequently against documented performance criteria.…”
Section: Historical and Current Cell Therapy Cryopreservationmentioning
confidence: 99%